WCET-aware prefetching of unlocked instruction caches: a technique for reconciling real-time guarantees and energy efficiency - Wuerges, Emílio (2015)
Tese (doutorado) - Universidade Federal de Santa Catarina, Centro Tecnológico, Programa de Pós-Graduação em Engenharia de Automação e Sistemas, Florianópolis, 2015.